Performance Analysis of Multi-Layered Clustering Routing Protocol for Wireless Sensor Networks - Kiran, W. S. (IRO Journal on Sustainable Wireless Systems, 2022)
Wireless Sensor Networks are the most efficient networks today, and they are used in many industrial, medical, and security applications. The major drawback of the sensor network is energy consumption due to the smaller size of the sensor node. To overcome the energy consumption, this paper proposes a new routing protocol called Multi-Layered Clustering Routing Protocol. This proposed routing protocol contributes to network’s long life and energy efficiency. During data transmission between the source and destination, the clustering approach is used in each layer. This assists in identifying the level of energy at each sensor node, which results in energy consumption reduction. Experimental results analyse the performance of the proposed routing protocol, that regulates the energy consumption and improves the network lifetime compared to the existing techniques.